2015
DOI: 10.1177/1555412015600580
|View full text |Cite
|
Sign up to set email alerts
|

Does Digital Gaming Enable Healthy Aging for Community-Dwelling People With Dementia?

Abstract: This article critically explores the benefits of commercial digital gaming technology for healthy aging of people with dementia. Research with community-dwelling people with dementia has highlighted the need for enhanced access to nonpharmacological interventions to support social engagement. Commercially available technologies offer a means to engage people with dementia. This article expands on this body of knowledge by assessing the benefits of digital gaming on healthy aging for community-dwelling people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(126 citation statements)
references
References 67 publications
1
125
0
Order By: Relevance
“…(2016) have shown, participants with dementia were able to learn complex movements and button combinations that relied on mental, physical, and fine motor skills. Their study participants were also able to develop this learning to acknowledge and correct mistakes, even before they were pointed out (Cutler et al, 2016). The findings of this study suggest that participants displayed a willingness and desire for continued learning, which shows that people with dementia are keen and able to partake in novel activities and learn new concepts, all of which are beneficial to their healthy aging (Cutler et al, 2016).…”
Section: Providing Digital Literacy Skills Through Leisure Educationmentioning
confidence: 76%
See 3 more Smart Citations
“…(2016) have shown, participants with dementia were able to learn complex movements and button combinations that relied on mental, physical, and fine motor skills. Their study participants were also able to develop this learning to acknowledge and correct mistakes, even before they were pointed out (Cutler et al, 2016). The findings of this study suggest that participants displayed a willingness and desire for continued learning, which shows that people with dementia are keen and able to partake in novel activities and learn new concepts, all of which are beneficial to their healthy aging (Cutler et al, 2016).…”
Section: Providing Digital Literacy Skills Through Leisure Educationmentioning
confidence: 76%
“…According to Liechty and Genoe (2013), using the Internet as a leisure resource helps older adults cope with retirement and the distance from their former social networks. Furthermore, some researchers also have found that digital gaming contributes to older adults social capital and provides three distinct benefits that promote healthy aging and independence for people living with dementia (Cutler, Hicks, & Innes, 2016).…”
Section: Computers and Tablets As A Leisure Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Cutler et al [1] employed a highly interactive mobile platform to enhance the communication abilities and positive emotions of elderly people. Through incorporating digital somatosensory games into reminiscence therapy, the researchers effectively enhanced users' healthy daily living activities and intergenerational interactions within their families, thereby generating positive perceptions.…”
Section: Introductionmentioning
confidence: 99%